THE EFFECT OF POLITICAL CONNECTIONS AND NATURE OF INDUSTRY ON FRAUDULENT FINANCIAL REPORTING - JISELLA NATALIE; IRWANTO HANDOJO; DICKY SUPRIATNA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
This research aims to obtain empirical evidence regarding the influence of financial targets, financial stability, external pressure, ineffective monitoring, nature of the industry, external auditor quality, board of directors' turnover, auditor turnover, frequent number of CEO’s picture, and political connections on fraudulent financial reporting. The object of this research is manufacturing companies listed on the Indonesia Stock Exchange during the 2021–2023 period, using a purposive sampling method, resulting in 197 data points. The data were analyzed using multiple linear regression with SPSS software. The results of the research show that financial targets, financial stability, and board of directors' turnover have a positive influence on fraudulent financial reporting. Meanwhile, the nature of the industry has a negative influence on fraudulent financial reporting. External pressure, ineffective monitoring, external auditor quality, auditor turnover, frequent number of CEO’s picture, and political connections do not significantly influence fraudulent financial reporting.